2013
DOI: 10.1080/15433714.2011.581545
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Evidence-Based Practice: Practitioner Assessment of an Agency-Based Training Program

Abstract: Little is known about evidence-based practice (EBP) in social service agencies beyond studies of researcher, practitioner, and educator opinions. The Bringing Evidence for Social Work Training (BEST) Project involved 16 participants from 3 social service agencies. The experiential training, delivered by 2 doctoral students, focused on a team-identified practice issue and followed the EBP process of motivation, question formulation, search, evaluation, and application planning. Posttraining focus group data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…For example, trained field instructors were more likely to identify their level of training as a facilitator to using RSTs. This finding is supported in prior research that has also emphasized the importance of training in uptake of empirically based treatment approaches (Berger, 2013;Bledsoe-Mansori et al, 2013;Wike et al, 2014). Other items rated higher for trained participants included the simplicity of implementing an intervention, the flexibility of the intervention to meet clients' needs, their ability to track long-term client outcomes, and their confidence in selecting RSTs for use.…”
Section: Barriers and Facilitators Of Rstssupporting
confidence: 70%
“…For example, trained field instructors were more likely to identify their level of training as a facilitator to using RSTs. This finding is supported in prior research that has also emphasized the importance of training in uptake of empirically based treatment approaches (Berger, 2013;Bledsoe-Mansori et al, 2013;Wike et al, 2014). Other items rated higher for trained participants included the simplicity of implementing an intervention, the flexibility of the intervention to meet clients' needs, their ability to track long-term client outcomes, and their confidence in selecting RSTs for use.…”
Section: Barriers and Facilitators Of Rstssupporting
confidence: 70%
“…Berger (2013) suggests this can be taught by breaking down the EBP process into manageable steps where students proceed through the stages deliberately while taking the time to process each step under supervision in their field education. Second, social work programs can partner with social service agencies to provide training on EBP, research assistance, and access to EBP information and materials to encourage and support current practitioners to continually engage in the EBP process (Bledsoe-Mansori et al, 2013). Finally, social work programs that provide continuing education to social work practitioners can ensure that the EBP process is integrated into the training to reinforce the use of EBP in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, even if practitioners have access to the best available research, the integration into clinical practice can be a slow and challenging process as the extent to which practitioners engage and apply the process of EBP with their clients has been found to vary based on numerous factors, such as time to engage in research and the EBP process, access to research, outside political or insurance pressure, organizational support, knowledge and skills of the practitioner, and ongoing training, support, mentorship, and supervision (Bellamy, Bledsoe, & Traube, 2006;Bledsoe-Mansori et al, 2013;Gray, Joy, Plath, & Webb, 2015;Morago, 2010;Tuten et al, 2016;Wharton, 2010). For example, social workers need time to search for and appraise evidence as part of the EBP process, which requires organizations to acknowledge and support such activities through dedicated staff time as well as access to libraries and online databases of research evidence.…”
mentioning
confidence: 99%
“…Consequently, the model might easily transfer to an agency-based EBP initiative, wherein the roles of students, faculty, and fieldwork instructors are those of practitioners, trainers, and supervisors, respectively. Implementation sustainability, which has historically been problematic in EBP initiatives (Bledsoe-Mansori, et al, 2013), might also be supported through the use of this model, which can be used to identify factors that promote sustained, systematic, and faithful use of EBPs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while fieldwork instructors may be receptive to EBP, organizational factors and the nature of their access to EBP information and training can influence how they approach, access information about, and implement EBP. Bledsoe-Mansori, et al (2013) found that their evidence-based agency training program was not sufficient to sustain its use in practice. Barriers included practitioners' lack of confidence in their ability or desire to carry out the tasks, difficulties in selecting alternative interventions and integrating empirical evidence with theoretical frameworks, technical challenges in conducting electronic searches, struggles evaluating the applicability and quality of evidence for agencies' unique practice questions and client populations, and difficulties using statistical methods to interpret the identified evidence.…”
Section: Barriers To Ebp In Social Workmentioning
confidence: 96%